Care planning in children and young people's nursing - Corkin, Doris; Clarke, Sonya; Liggett, Lorna (Wiley-Blackwell, 2011)
Care Planning in Children and Young People's Nursing addresses a selection of the most common concerns that arise when planning care for infants, children and young people within the hospital and community setting. Clear and detailed this text utilizes images and case studies to provide a holistic insight into the practice of care planning through the report of current research, best available evidence, policy and education which reflects both the uniqueness and diversity of contemporary children's nursing.